Who posted #MeToo, why, and what happened: A mixed methods examination - Siuta, Rose L.; Martin, Robert C.; Dray, Kelly K.; Liu, S.-N. Cindy; Bergman, Mindy E. (Frontiers in Public Health, 2023)
Objectives: The #MeToo social media campaign raised awareness about sexual harassment. The purpose of the current study was to address three unexplored research questions. First, what factors influenced whether a person posted #MeToo? Second, how did posting (or not) influence participants’ well-being? Finally, what motivated participants’ posting (or not) #MeToo? Method: This mixed-methods study explores how #MeToo was experienced by full-time employees (N = 395) who could have posted #MeToo (i.e., experienced a sexual harassment event), whether or not they did so. Participants completed surveys in July of 2018 assessing social media use, sexual harassment history, relational variables such as relative power and social support, and job and life satisfaction. Participants also responded to open-ended survey questions about the context of and decisions about #MeToo posting. Results: Quantitative results indicated that sexual harassment history was the most powerful predictor of #MeToo posting, while power and interpersonal contact also contributed. Qualitative analyses (N = 74) using a grounded theory approach indicated themes associated with decisions to disclose, including feeling a responsibility to post, need for support, and affective benefits. Decisions not to disclose were event-related negative affect, posting-related negative affect, timing of the event, fit with the #MeToo movement, privacy concerns, and fear of consequences. Conclusion: This study contributes to the literature on sexual harassment disclosure by focusing on informal means of disclosure and drawing on comparisons to formal reporting and implications for workplaces. Online sexual harassment disclosure, in many ways, reflects the impediments to formal reporting procedures. Given the increased use of social media for purposes of disclosure, these findings suggests that organizations should recognize the legitimacy of sexual harassment reports made online and consider the possible failings of their formal reporting systems as reasons for online disclosure.